Výpočet mapy disparity z barevných stereo snímků - Kulíková, Barbora (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2016)
Tato bakalářská práce se věnuje tvorbě disparitních map. První kapitoly jsou zaměřeny na fyziologii lidského vnímání prostoru a metodách zobrazení 3D obsahu, což jsou témata blízce související s disparitní mapou, jejím vznikem a praktickým využitím. Následuje popis používaných metod zpracování obrazu. Stěžejní teoretická kapitola pojednává o metodách výpočtu disparitní mapy a použitých principech. V praktické části byla vytvořena aplikace s uživatelským rozhraním v prostředí MATLAB. Aplikace umožňuje tvorbu disparitních map pomocí lokálních a globálních metod. Funkčnost aplikace a implementace metod je experimentálně ověřena a byl proveden experiment srovnávající jednotlivé metody a zkoumající vliv parametrů lokální metody na kvalitu disparitní mapy. Součástí práce bylo vytvoření jednoduché databáze stereosnímků.

This bachelor’s thesis deals with a creation of the depth maps. The first chapter concerns with the physiology of a human space perception and the methods of displaying the 3D content which are the topics closely related to the depth map, its creation and practical usage. Subsequently, there is a chapter focused on the description of the used methods of the image processing. The fundamental theoretical chapter deals with the methods of computing the disparity and used principles. In the practical part of the thesis an application has been made with a user interface in the Matlab environment. The application enables the user to create the disparity maps through the local and global methods. The functionalism of the application and the implementation of the methods are experimentaly verified. An experiment comparing the methods and analyzing influence of the local method parameters on the quality of the depth map has been made. The last part of the thesis was to create a simple stereopicture database.
Calculating disparity map from color stereo images
Keywords: Disparity; disparitní mapa; hloubková mapa; stereoskopie; MI; SSIM; CGRAD; Depth Discontinuities by Pixel-to-Pixel Stereo; SSD; Disparity; disparity map; depth map; stereoscopy; representation of the image; MI; SSIM; CGRAD; Depth Discontinuities by Pixel-to-Pixel Stereo; SSD